2015
DOI: 10.1111/jep.12366
|View full text |Cite
|
Sign up to set email alerts
|

Can nurses be key players in assessing early motor development using a structured method in the child health setting?

Abstract: Despite brief experience with SOMP-I, the agreement was excellent when assessing the level of motor development, but was less satisfactory for the assessment of quality of motor performance. More extensive education and training may be necessary to improve the nurses' ability to assess quality, as this domain was an entirely new concept to the nurses. Further research is warranted to determine the applicability of SOMP-I as a standardized method for nurses to assess motor development within the CHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…The course comprised general information about the method and training through assessments of infants by video‐observation and discussion. Prior to the present study, the nurses took part in an initial trial applying the method in their own centres to assess the motor performance at regular well‐baby visits [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The course comprised general information about the method and training through assessments of infants by video‐observation and discussion. Prior to the present study, the nurses took part in an initial trial applying the method in their own centres to assess the motor performance at regular well‐baby visits [22].…”
Section: Methodsmentioning
confidence: 99%
“…Within the CHS, the nurses have a key medical role and are the primary care providers for the child and her/his family [10]. In a previous study, we therefore tested if child health nurses were able to assess early motor development according to the SOMP-I, and we found that despite having only brief experience with the method, nurses were able to perform a structured assessment of the motor performance in a clinical setting [22]. Implementation science has shown that significant barriers exist to the introduction and maintenance of new methods in routine practice [14,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one cannot rule out that an even closer collaboration between the PTs and the public health nurses may prevent some of these referrals. In Sweden, there is an example of implementation of a screening tool to support the nurses in clinical decision making regarding when to be concerned about motor development (5). In our study, there was a great overlap between referral causes and the PT's functional diagnoses regarding concerns for motor development and asymmetry, indicating that different professionals in Trondheim Municipality evaluate these conditions similarly.…”
Section: Discussionmentioning
confidence: 74%
“…Previously, we have investigated the method’s reliability and some aspects of clinical utility when used by nurses in the child healthcare setting[62,63]. Despite having only brief training and experience with SOMP-I, nurses were able to reliably assess the level of motor development, while more variability was found when assessing the quality of motor performance[63].…”
Section: Introductionmentioning
confidence: 99%
“…Despite having only brief training and experience with SOMP-I, nurses were able to reliably assess the level of motor development, while more variability was found when assessing the quality of motor performance[63]. In focus group interviews, the child health nurses expressed that learning the method was relevant and provided them with a tool to master a central task in their daily clinical practice[62].…”
Section: Introductionmentioning
confidence: 99%